Contractual Ethics Analysis of the Phenomenon of non-Transactional Consumption in Cafes: The Perspective of Islamic Economic and Justice - Asharsyira, Almeyda; Andriansyah, Yuli; Martins, José Moleiro (IAIN Manado, 2026)
This study examines the increasingly common phenomenon of non-transactional consumption in cafes, known locally as